Biofeedback therapy for anorectal functional disorder: Malaysian colorectal tertiary centre experience - Saidah Sahid; Muhd Yusairi Kamarulzaman; Johari Mustafa; Nik Amin Sahid Nik Lah; Nil Amri Mohamed Kamil (Elsevier Ltd, 2022)
Background: Anorectal functional disorder encompasses arrays of conditions including Obstructive Defecation Syndrome (ODS) and Fecal Incontinence (FI). Biofeedback Therapy (BFT) serves as first line therapy to re-train pelvic floor coordination, rectal sensation and strengthening pelvic floor muscle. The aim of this study is determining the efficacy of BFT in our centre. Methods: This is a retrospective observational cohort study of patients attended biofeedback therapy session from January 2013 to December 2018. Descriptive statistic was used to analyse the data. Result: Total 99 patients with mean age of 44.6 ± 18.1 with female 56% (n = 55) and male 44% (n = 44) attended BFT session. Overall, 77 had CC (77%) and 23 (23%) had FI. Mean number of sessions was 11.8. Overall improvement rate 42 (42%), no improvement 32 (32%) and defaulted 26 (26%). In patients with CC, 32 (41.6%) had improvement in symptoms, 23 (29.9%) had no improvements, 22 (28.6%) defaulted BFT. Patients with FI, 7 (30.4%) had Obstetric Sphincter Injury, 7 (30.4%) had traumatic anal injury, 3 (13.0%) has Low Anterior Resection Syndrome, 2 (8.7%) had sphincter injury following anal sepsis, 2 (13.0%) had rectocele repair and 1 (4.3%) were idiopathic. 9 patients (39.1%) had stoma created. Overall response rate was: 10 patients (43.5%) had improvement in symptoms, 9 patients (39.1%) had no improvement, 4 patients (17.4%) defaulted therapy. Conclusion: Our outcome rate is lower compared to published due the limited access and logistic restrictions. This issue should be given great consideration such as broadening the service and training.